Mortgage indebtedness and household financial distress - Dimitris Georgarakos; Adriana Lojschová; Melanie Ward-Warmedinger (European Central Bank (ECB), 2010)
Using comparable survey data from twelve European countries from 1994 to 2001 we investigate households' attitudes towards mortgage indebtedness. We find that a given debt burden creates much higher distress in countries with fewer mortgage holders relative to countries where a significant part of households uses mortgage debt. This effect is net of ppp-adjusted income levels, various socioeconomic characteristics, housing traits, country-specific constant terms, and household unobserved heterogeneity. We show that households evaluate their own debt burden partly in comparison with the debt position of their peer group and in a way consistent with social stigma considerations which lessen in significance as markets expand.
Keywords: D12; D14; G21; 330; credit markets; financial distress; Household finance; Mortgage debt; peer effects; Hypothek; Private Verschuldung; Liquiditätsbeschränkung; Soziale Beziehungen; Kreditmarkt; Marktliquidität; Europa